2017
DOI: 10.4329/wjr.v9.i11.405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seldinger and trocar techniques in the percutaneous treatment of hydatid cysts

Abstract: AIMTo comparatively evaluate Seldinger and Trocar techniques in the percutaneous treatment of hydatid disease.METHODSTrocar and Seldinger techniques were used for 49 and 56 cysts, respectively, among 106 hydatid cysts in 88 patients. The number of males and females were 22 and 66, respectively with a mean age of 44.9 years (range, 15-87). Follow-up studies included cyst diameter, cyst contents, and morphological changes in the cyst wall, local recurrence, and secondary invasion, using ultrasound, computerized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Most patients received one drainage per intervention. The trocar technique as a single-step procedure is easier and more economical to apply compared with the drainage procedure conducted using Seldinger techniques and was more frequently used in our patients [ 22 ]. As the postoperative fluid collections were mostly superficial, direct access (67.5%) was more frequently used than transhepatic (32.0%) or transpleural access (0.5%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients received one drainage per intervention. The trocar technique as a single-step procedure is easier and more economical to apply compared with the drainage procedure conducted using Seldinger techniques and was more frequently used in our patients [ 22 ]. As the postoperative fluid collections were mostly superficial, direct access (67.5%) was more frequently used than transhepatic (32.0%) or transpleural access (0.5%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Turan et al conducted a study comparing two percutaneous techniques and found a complication rate of 6.1% in the trocar technique and 17.9% in the Seldinger technique. There was no significant difference between the two techniques in terms of complications and recurrence 22 . We found it more accurate to compare the two techniques by including all complications during and after percutaneous treatment and in the long term.…”
Section: Discussionmentioning
confidence: 73%
“…There were no differences among that techniques. 20 To our best knowledge, the present study is the largest case series for the percutaneous treatment of hydatic cyst in a single center.…”
Section: Discussionmentioning
confidence: 81%
“…Developing cavity infection or abscess were reported to be between 5.6%-26.9% in the literature. [18][19][20][21][22][23] There are several advantages of the Ormeci technique over the PAIR(18) (Table 4). We did not have any patients who had abscess or infection in the cyst cavity.…”
Section: Discussionmentioning
confidence: 99%